The Individual and the Welfare State 2011
DOI: 10.1007/978-3-642-17472-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Childhood, Schooling and Income Inequality

Abstract: Parental socio-economic background plays an important role in determining employment outcomes during the individual’s whole life-cycle. Indeed, the environment in which individuals grow up plays a crucial role in determining their later socio-economic condition, regardless of their own abilities. On the one hand, this link might be due to the transmission of social norms (e.g. work ethics) or risk attitudes from parents to children. On the other hand, public policies may strengthen or weaken cross-generational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
0
12
0
2
Order By: Relevance
“…Future research could examine the role of pathways other than SES and health, by including other potentially relevant adverse childhood exposures such as abuse, family conflict and disruption (Blane et al 2012 ; Brandt et al 2012 ). Pathways may also include advantageous exposures such as childhood happiness (Bellis et al 2013 ), parental care (Huppert et al 2010 ), and cultural capital (De Graaf et al 2000 ; Jæger 2009 ), which may partly explain the direct effect books at home had on later quality of life (Cavapozzi et al 2011 ). The effect of books on later quality of life is particularly interesting and is consistent with prior research showing that this marker of cultural capital confers additional advantages beyond parental education, occupation and social class, perhaps because it reflects, alongside other advantages, a scholarly culture including the promotion of skills and competencies that are directly useful for learning and education, and a preference for and enjoyment of scholarly pursuits (Evans et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research could examine the role of pathways other than SES and health, by including other potentially relevant adverse childhood exposures such as abuse, family conflict and disruption (Blane et al 2012 ; Brandt et al 2012 ). Pathways may also include advantageous exposures such as childhood happiness (Bellis et al 2013 ), parental care (Huppert et al 2010 ), and cultural capital (De Graaf et al 2000 ; Jæger 2009 ), which may partly explain the direct effect books at home had on later quality of life (Cavapozzi et al 2011 ). The effect of books on later quality of life is particularly interesting and is consistent with prior research showing that this marker of cultural capital confers additional advantages beyond parental education, occupation and social class, perhaps because it reflects, alongside other advantages, a scholarly culture including the promotion of skills and competencies that are directly useful for learning and education, and a preference for and enjoyment of scholarly pursuits (Evans et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…As with other international socioeconomic indices, it is moderately correlated with education and income levels (see McMillan et al 2009 for further details). Access to books at home is a childhood SES indicator from both ELSA and SHARE life history surveys, which reflects the educational level, cultural capital, and scholarly culture of adults in the household (Cavapozzi et al 2011 ; Evans et al 2010 ). A single item asked ‘About how many books were there in your home?’ with five response options: 1 = None or very few, 2 = Enough to fill one shelf, 3 = Enough to fill one bookcase, 4 = Enough to fill two bookcases, 5 = Enough to fill three or more bookcases.…”
Section: Methodsmentioning
confidence: 99%
“…The number of books available in the childhood home has been frequently used as an important indicator of the intellectual and educational background of family; with their availability usually measured in terms of number of shelves/ bookcases filled with books (Cavapozzi, Garrouste, & Paccagnella, 2011;Dal Bianco et al, 2013;Flores & Kalwij, 2014;Mazzonna & Havari, 2011). Studies have reported that the better the…”
Section: Booksmentioning
confidence: 99%
“…There is a growing body of literature showing the significance of major events experienced by individuals in the past for their current socio‐economic outcomes in different historical contexts (for example, Attanasio et al ., ; Cavapozzi et al ., ; Deindl, ; Kesternich et al ., ). In Section 3 we showed how SHARELIFE data can be used to examine the dynamics of the labour market in Poland at the time of the economic transition.…”
Section: Analyzing Long‐term Consequences Of Economic Shocksmentioning
confidence: 99%